2010
DOI: 10.1016/j.tcm.2011.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Biology of Microsomal Prostaglandin E Synthase-1

Abstract: Both traditional and purpose designed nonsteroidal anti-inflammatory drugs (NSAIDs), selective for inhibition of cyclooxygenase (COX) -2 alleviate pain and inflammation but confer a cardiovascular hazard, attributable to inhibition of COX-2 derived prostacyclin (PGI2). Deletion of microsomal PGE synthase–1 (mPGES-1), the dominant enzyme that converts the COX derived intermediate product, PGH2, to form PGE2, modulates inflammatory pain in rodents. By contrast with COX-2 deletion or inhibition, PGI2 formation is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 66 publications
(85 reference statements)
0
42
0
2
Order By: Relevance
“…mPGES-1 is a key enzyme in inflammation, pyresis, hyperalgesia and multiple diseases with inflammatory component including rheumatoid arthritis and osteoarthritis, periodontitis, atherosclerosis, inflammatory kidney damage, stroke, multiple sclerosis and Alzheimer's disease as summarized in several excellent reviews [4,6,11,13]. Still under debate is whether mPGES-1 inhibition achieves comparable analgesic efficiency to COX inhibition since PGH 2 is redirected towards alternative pain sensitizing prostanoids, in particular PGI 2…”
Section: Mpges-1mentioning
confidence: 99%
See 2 more Smart Citations
“…mPGES-1 is a key enzyme in inflammation, pyresis, hyperalgesia and multiple diseases with inflammatory component including rheumatoid arthritis and osteoarthritis, periodontitis, atherosclerosis, inflammatory kidney damage, stroke, multiple sclerosis and Alzheimer's disease as summarized in several excellent reviews [4,6,11,13]. Still under debate is whether mPGES-1 inhibition achieves comparable analgesic efficiency to COX inhibition since PGH 2 is redirected towards alternative pain sensitizing prostanoids, in particular PGI 2…”
Section: Mpges-1mentioning
confidence: 99%
“…Moreover, deletion of mPGES-1 reduced the diuretic response to acute water loading [23] and increased urine concentration after water deprivation [24] while diminishing natriuresis [25]. To which extend mPGES-1 is required to excrete an acute enteral load of sodium chloride and whether this has impact on the blood pressure is controversially discussed [13,20].…”
Section: Page 9 Of 59mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies which demonstrated that the enzyme converting PGH2 to PGE2, the socalled microsomal prostaglandin E synthase-1 (mPGE-1), is overexpressed in inflammation and couples with COX2 to enhance PGE2 generation. This has led more recently to the suggestion that selective inhibitors of this enzyme may be an important therapeutic target that will result in selective inhibition of the pathological PGE2, allowing PGH2 to be converted into the physiologically active prostaglandin, prostacyclin (45,46) . Overexpression of mPGE-1 has been shown in different forms of cancers and its presence is significantly correlated with a worse prognosis, at least in colorectal cancers (47,48) .…”
Section: The Vascular Endotheliummentioning
confidence: 99%
“…However, mPGES-1 inhibitors differ from COX inhibitors with respect to where in the biosynthetic cascade they inhibit PGE 2 production. It has been hypothesized that mPGES-1 inhibitors might exhibit better safety profiles due to their propensity to affect the formation of other eicosanoids than PGE 2 in a different way than conventional NSAIDs and COX-2 inhibitors (Samuelsson et al, 2007;Wang and FitzGerald 2010). However, this might also have consequences for the translational aspects of PGE 2 inhibition in pain relief (Wang and FitzGerald 2010).…”
Section: Introductionmentioning
confidence: 99%